A novel decoupled time-variant reliability-based design optimization approach by improved extreme value moment method. (January 2023) - Zhao, Zhao; Zhao, Yan-Gang; Li, Pei-Pei
Highlights: Time-variant reliability constraints are considered by the improved extreme value moment method. Local approximation of extreme value moment is established using WA-SGNI. A local approximation method for quantile functions is proposed. A decoupled t-RBDO method is developed by combining sequential approximation optimization. Abstract: Time-variant reliability-based design optimization (t-RBDO) is an effective tool to guarantee a high reliability of the product during the full life cycle. This paper proposes a new decoupled method for t-RBDO via an improved extreme value moment method (EVMM). In the proposed method, a weight approach based on sparse grid numerical integration (WA-SGNI) is employed to establish the local approximation of the extreme value moment. Since evaluating the failure probability functions (FPFs) using fourth-moment transformation method has certain limitations, a local approximation method for quantile functions (QFs) is proposed to consider the time-variant reliability constraints in t-RBDO. After the local approximations of QFs are established, t-RBDO problem is decoupled into a deterministic one in the design sub-region. Combining sequential approximation optimization, a unified t-RBDO framework is presented. Four numerical examples are investigated to validate the accuracy and efficiency of the proposed method.